The Mouse Gut Microbial Biobank expands the coverage of cultured bacteria - Chang Liu (Nature Portfolio, 2020)
Here, the authors established and characterized the mouse gut microbial biobank (mGMB), which includes 244 strains and 126 species that enlarges previous mouse intestinal bacterial collections and represents a resource for studies using mouse models to investigate microbiome-associated health and disease.